Isolation of ancestral sylvatic Dengue virus type 1, Malaysia - Teoh, B.T.; Sam, S.S.; Abd-Jamil, J.; AbuBakar, Sazaly (2010)
Ancestral sylvatic dengue virus type 1, which was isolated from a monkey in 1972, was isolated from a patient with dengue fever in Malaysia. The virus is neutralized by serum of patients with endemic DENV-1 infection. Rare isolation of this virus suggests a limited spillover infection from an otherwise restricted sylvatic cycle.